Assessing the Impact of a Proactive Personality on Early Employment Status and Job Search Behavior: The Role of Career Planning and the Moderating Effect of Core Self-Evaluation - Hafiz Ghufran Ali Khan; Omer Azam; Syed Yaseen (The Lahore Journal of Business)
This study ascertains the conditional indirect effects of core self-evaluation and career planning, particularly regarding early employment status and job search behavior based on the theory of planned behavior. For this purpose, we collected data from 400 respondents using the simple random sampling method. The results reveal that most young graduates have early career success if they possess initiative and a thoughtful disposition and demonstrate rigorous job-seeking behavior. Young people can access early employment opportunities if they adopt a proactive approach toward their careers. Effective career planning with active career searching behavior, supplemented by high levels of core self-evaluation, can increase chances of early career success. Moreover, our findings have practical implications for young people in terms of encouraging them to plan their careers in a more organized and proactive manner.